Analisis Ekspor Pakaian Muslimah Indonesia ke Malaysia: Peluang, Daya Saing, dan Strategi Peningkatan Perdagangan Periode 2025 - Mutiara Zahra Bilqis (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the performance and opportunities of Indonesian Muslim fashion (pakaian muslimah) exports to Malaysia in the 2025 period. Using secondary data from the Central Bureau of Statistics (BPS), the Trade Policy Agency (BKPerdag), and ITC Trademap, this descriptive quantitative research reveals that Malaysia is the second largest destination for Indonesia's non-oil and gas exports at US11.72 billion (up 8.44 percent), and a key market for textile and apparel products including Muslim fashion. Indonesia's total textile and apparel exports from the manufacturing sector reached US227.10 billion in 2025, up 14.47 percent. Malaysia's Muslim population—representing approximately 63 percent of its 33 million inhabitants—creates substantial and sustained demand for halal-compliant fashion products. The IUAE-CEPA model and the RCEP framework provide strategic instruments for Indonesia to expand its Muslim fashion market share in Malaysia. Challenges include competition from China, Bangladesh, and Turkey, as well as regulatory compliance. Recommendations focus on brand development, RCEP tariff optimization, e-commerce penetration, and halal certification strengthening.